2011
DOI: 10.1097/opx.0b013e31822a61e7
|View full text |Cite
|
Sign up to set email alerts
|

Abandonment of Low-Vision Devices in an Outpatient Population

Abstract: Purpose To investigate abandonment rate of prescribed low vision devices for near tasks and factors associated with abandonment in a U.S. outpatient population. Methods A telephone survey was administered to 88 patients with low vision from four clinical sites approximately one year after examination and prescription of devices. Patients were surveyed on timing and frequency of use and reasons for abandonment of devices. The main outcome measure (abandonment) was defined as patient report of no use of prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 21 publications
4
44
0
1
Order By: Relevance
“…Only 71% were reportedly used in the prior week. Reasons for abandonment were similar to those reported by veterans 12 , including a different device was used for the task, the device was ineffective for the task or the patient’s vision had worsened 14 . Device abandonment was not associated with age, gender, visual acuity, training, study center or diagnosis.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Only 71% were reportedly used in the prior week. Reasons for abandonment were similar to those reported by veterans 12 , including a different device was used for the task, the device was ineffective for the task or the patient’s vision had worsened 14 . Device abandonment was not associated with age, gender, visual acuity, training, study center or diagnosis.…”
supporting
confidence: 61%
“…Our findings are consistent with previous research on device use and persons with low vision. 1114 We are not aware of any other published studies of device use among patients with AMD undertaken since anti-VEGF treatments came into widespread use. The patients enrolled in this study were seen since 2008, when those treatments were broadly available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dougherty et al [13] identified that low-vision devices are not used by the target group. On reason for this abandonment could be that the devices do not match the users' needs.…”
Section: Related Workmentioning
confidence: 99%
“…Among these devices, handheld magnifiers are the most commonly prescribed and electronic magnifiers are the least. 5 All of these devices are still utilised a great deal among the visually impaired population. However, limitations exist with all these devices.…”
Section: Introductionmentioning
confidence: 99%